2014
DOI: 10.1007/s13311-014-0279-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for the Treatment of Epilepsy: Circuits, Targets, and Trials

Abstract: Deep brain stimulation (DBS) has proven remarkably safe and effective in the treatment of movement disorders. As a result, it is being increasingly applied to a range of neurologic and psychiatric disorders, including medically refractory epilepsy. This review will examine the use of DBS in epilepsy, including known targets, mechanisms of neuromodulation and seizure control, published clinical evidence, and novel technologies. Cortical and deep neuromodulation for epilepsy has a long experimental history, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 123 publications
0
87
0
2
Order By: Relevance
“…Along the same line, novel perspectives are foreseen in clinical approaches for testing neurostimulations (Kahane and Depaulis, 2010). There is indeed a growing interest in epileptology for alternative therapeutic strategies aimed at modulating the electrical brain activity via direct or indirect stimulation of the epileptic regions (Fisher, 2013;Laxpati et al, 2014;Mina et al, 2013). Computational models may help us to determine the key structures to stimulate and to find the optimal stimulation parameters.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Along the same line, novel perspectives are foreseen in clinical approaches for testing neurostimulations (Kahane and Depaulis, 2010). There is indeed a growing interest in epileptology for alternative therapeutic strategies aimed at modulating the electrical brain activity via direct or indirect stimulation of the epileptic regions (Fisher, 2013;Laxpati et al, 2014;Mina et al, 2013). Computational models may help us to determine the key structures to stimulate and to find the optimal stimulation parameters.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Ce type de traitement revêt un caractère définitif, se traduisant au mieux par la diminution ou l'arrêt des crises, mais pouvant également s'accompagner d'un certain nombre de déficits post-opératoires persistants. L'utilisation de la SCP pour le traitement de l'épilepsie pharmaco-résistante a fait l'objet de plusieurs dizaines d'études chez l'homme au cours des dix dernières années [42], mais seule l'efficacité de la stimulation du noyau antérieur du thalamus pour le traitement des épilepsies focales a véritablement été démon-trée jusqu'à présent [43]. Bien que les mécanismes d'action de la SCP soient encore mal connus, ce type de traitement est susceptible de diminuer la sévérité et la fréquence des crises de plusieurs manières : en normalisant directement l'activité du foyer épileptique, en agissant au niveau des voies et noeuds de propagation de l'activité épileptique, ou enfin en activant des mécanismes de plasticité ayant pour effet de diminuer l'excitabilité des circuits épileptogènes.…”
Section: Approches Optogénétiques Dans Le Traitement De L'épilepsieunclassified
“…Epilepsy affects 1% of population in the world, and 30-40% of cases are medically refractory [61][62][63][64][65]. Management of patients who have recurrent seizures and did not respond to medication or surgery is challenging.…”
Section: Neuromodulation For Epilepsymentioning
confidence: 99%
“…A review study also found DBS effective in reducing seizure frequency [70]. The target areas of DBS for treatment of epilepsy include Anterior Nucleus [AN] of thalamus [71][72][73] [82,83], and the DBS -by the regulatory agencies in Canada, Europe, Australia, and elsewhere [61]. However,DBS is still in its early stage as a therapy for epilepsy.…”
Section: Neuromodulation For Epilepsymentioning
confidence: 99%